Legal Education and COVID-19: Current and Post-Pandemic Changes (Global Journal of Human-Social Science, 2025)
This paper aims to analyze legal education in times of COVID-19. It is indisputable that Law Schools must prepare students for a world in constant transformation. The ways of learning have undergone notable changes with the COVID-19 pandemic and technology is increasingly present in schools. Access to knowledge is more available to social actors and distance learning has become a reality for Law Courses. This is a descriptive literature review study, of a qualitative nature, on legal education in times of COVID-19 with relevant guidelines for teachers and students in light of the recommendations of the Ministry of Education.
Keywords: legal education; learning; distance education; COVID-19